Construction and Validation of the Proposal for Safety and Emergency Material and Equipment in Mountain Sports - Carlos Daniel Gomes Mata; Catarina Pereira; Luís Carvalhinho (Karger Publishers, 2023)
Introduction: This study aimed to build and validate a proposal for safety and emergency material and equipment adjusted to the practice of mountain sports in Portugal. The proposal was developed through documentary analysis, literature review, and expert consultation. Methods: The validation of the contents of the proposal was carried out using the Delphi technique, with the participation of 30 experts, male (N = 18) and female (N = 12), aged between 32 and 61 years (M = 42.50; SD = 7.29), with a mean of 16.63 ± 5.60 years of experience, divided into 4 groups: (i) pre-hospital trainers; (ii) pre-hospital nurses; (iii) pre-hospital physicians; (iv) higher education teachers in the field of mountain sports. The 1st version of the proposal was structured in 7 areas and included 29 items (material and/or equipment). The final version of the proposal was structured in 8 areas (general material, measuring equipment, burns, trauma, respiratory, medication, communications, and survival kit) and included 44 items (material and equipment). Results: The proposal showed Content Validity Index (CVI) values of 100%. Concerning the reliability and validity of the proposal, intraclass correlation coefficient values of 0.986 (excellent) were found for technical importance and 0.983 (excellent) for contextual fit. All values show a high level of inter-expert agreement. Conclusion: The validated proposal will be an appropriate tool for mountain sports technicians to use in order to promote safety, reduce accidents and their consequent morbidity, and reduce the activation of rescue teams.